Parenting Patterns in Kenagarian Koto Kaciak, Tanjung Raya District, Agam District - Rahmatul Friza; Linda Yarni (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
This research departs from the phenomenon that occurs in families in the Kenagarian Koto Kaciak area, Tanjung Raya District, Agam Regency, the majority of the population in this area is of productive age, most of them are busy with their own work so they pay less attention and control over their children's development. Even though they have families and children who still need guidance, direction and love. One of the causes of children's behavior that is deviant or not in accordance with applicable rules is inappropriate parenting patterns in the family, as well as parents' lack of education and knowledge about religion. This can be seen from the treatment of parents towards their children. This research is research (file research) which is descriptive qualitative in nature. The key informants in this research were parents and the supporting informants were 10 teenagers. Data collection techniques were obtained through observation and interviews. The collected data was analyzed using data analysis techniques sourced from observations and interviews. The validity of the data obtained was tested using triangulation. Based on the research results, it can be concluded that the parenting style applied by parents will influence children's attitudes and behavior both in the family, social and community environments. If the parenting style is right, then the behavior displayed by the child will be in accordance with what the parents expect and vice versa, the child's behavior will be deviant and contrary to existing rules. All of this is influenced by parents' busy lives which results in a lack of attention to children in controlling their development, relationships and daily life. The efforts made by parents are trying to implement appropriate parenting patterns according to their children's development and trying to pay more attention, providing good guidance and direction in living their daily lives to their children, so that children realize that they live within the rules. which must be obeyed and have a sense of responsibility.